Enhancing Students’ Problem-Solving Skills on Environmental Change through Cooperative Integrated Reading and Composition (CIRC) Assisted by Mind Mapping - Rifaatul Muthmainnah; Asep Rohayat; Alex Hidayat (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
This study examined the effect of Cooperative Integrated Reading and Composition (CIRC) assisted by mind mapping on students’ problem-solving skills in the context of environmental change. A quasi-experimental non-equivalent control group design was conducted with 74 tenth-grade students at a senior high school in Garut, Indonesia. The experimental group received CIRC combined with mind mapping, while the control group experienced teacher-centered instruction. The results showed no significant difference at the pre-test stage, indicating comparable initial abilities. However, the experimental group demonstrated significantly higher post-test scores, with a very large effect size (Cohen’s d = 1.31). A dimensional analysis revealed that the intervention enhanced students’ ability to clearly identify environmental problems, explain cause and effect relationships, and predict ecological consequences. The most substantial improvement was observed in generating and justifying solutions, where students produced more feasible, creative, and scientifically grounded responses. These findings suggest that integrating CIRC with mind mapping effectively supports the development of higher-order problem-solving skills. This approach promotes deeper analytical thinking and equips students to address complex socioscientific issues, highlighting its value as an innovative strategy in biology education